The CONSORT statement for cluster randomised trials - Campbell, M; Elbourne, DR; Altman, D (2005)
With the publication of the CONSORT statement there is now increased awareness of the need to adequately report the findings of randomised controlled trials. The CONSORT statement includes a checklist of items that should be addressed in the trial report. The original CONSORT statement was developed to ensure the appropriate reporting of parallel group randomised controlled trials in which individual participants are allocated to different intervention groups. In cluster randomised trials, however, groups of participants, rather than individuals, are randomly allocated to study groups. The process of allocating groups of participants raises additional reporting considerations and led to the publication of an extension to the CONSORT statement specifically for cluster randomised trials. In this paper we review the CONSORT extension to cluster randomised trials, outlining the special features of the cluster randomised trial which must be considered.